Quality of life measuring instruments related to oral health (Research, Society and Development, 2023)
Introduction: Oral health-related quality of life (OHRQOL) has been conceptualized as the impact of oral diseases on aspects of daily life that are important to people, with the impacts being of sufficient magnitude, either in terms of frequency, severity, or duration, to affect an individual's perception of their life in general. Objective: Gather the instruments used to measure quality of life related to oral health. Method: In Scielo databases, the studies were selected by reading the titles and abstracts, then read in full, and those that met the eligibility criteria were included. Next, the collected data was analyzed and interpreted. Results: We analyzed full articles from the year 2021 (n: 69) in the Scielo database. The table used 28 scientific articles (40.58%), and the most prevalent type of study was cross- sectional (39.28%). In relation to the instruments in specific, the most explored instrument in the analyses of QL related to dentistry was the OHIP-14 (34.48%): Conclusion: Given the above, it is observed that the knowledge of QL is of utmost importance for the DC, the instruments that measure QL are important tools to foster public policies in addition to showing the reality exposed by the patient himself in the questionnaires.